Association of FTO and TMEM18 polymorphisms with overweight and obesity in the population of Polish children - Rosset, Iwona; Strapagiel, Dominik; Sitek, Aneta; Majewska, Małgorzata; Ostrowska-Nawarycz, Lidia; Żądzińska, Elżbieta (Anthropological Review, 2016)
The objective of the study was to verify whether or not FTO rs9939609, rs9926289 and TMEM18 rs4854344, rs6548238, rs2867125 variants are important risk factors for overweight and/or obesity in Polish children aged 6-16 (n=283). FTO rs 9939609 and rs9926289 exhibited a strong codominant obesity-predisposing effect of genotypes homozygous for minor alleles (OR=5.42, 95% CI: 2.04-14.39, p=0.0006). The important finding of the study is increased risk of overweight (OR=5.03, 95% CI: 1.15-21.93, p=0.0306) in individuals homozygous for the minor alleles rs4854344, rs6548238 and rs2867125 in the recessive inheritance model, while no other significant associations between TMEM18 variants and risk of obesity were found. Given the identified interaction TMEM18 genotype × BMI category (p=0.0077), it seems that the effect of homozygous for the minor alleles may be compared to a “weight guard”, which significantly increases the risk of overweight, but not of obesity, because it promotes weight gain only up to the threshold of obesity. Conclusion: The proposed hypothetical effect (“weight guard”) of homozygous for the minor alleles in the TMEM18 based on a rather small sample is a possible explanation of the effects of minor alleles, which minimize the risk of obesity.